1935
DOI: 10.1017/s0305004100013633
|View full text |Cite
|
Sign up to set email alerts
|

Some Experiments with Neutrons slowed down at different Temperatures

Abstract: Experiments are described comparing the effects of neutrons slowed down in paraffin wax at the temperatures of liquid nitrogen and liquid hydrogen with those obtained at ordinary temperatures. It is found that the absorption produced by certain substances increases as the temperature is lowered. The transformations produced in these substances also increase, but generally to a smaller extent, probably owing to more neutrons being absorbed in the paraffin: the exact figure depends on the thickness of the layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1936
1936
1938
1938

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…the liquid covering the block, as the space round the block was very thin, and the presence there of liquid hydrogen (density 0-07 g./cm. 3 ) was not found to produce any measurable change in the effects. Experiments by Westcott and Niewodniczanski (3) with boric acid solutions had shown that the slow neutrons emerging in the neighbourhood of the detector (D, Fig.…”
Section: Experimental Arrangementmentioning
confidence: 79%
See 2 more Smart Citations
“…the liquid covering the block, as the space round the block was very thin, and the presence there of liquid hydrogen (density 0-07 g./cm. 3 ) was not found to produce any measurable change in the effects. Experiments by Westcott and Niewodniczanski (3) with boric acid solutions had shown that the slow neutrons emerging in the neighbourhood of the detector (D, Fig.…”
Section: Experimental Arrangementmentioning
confidence: 79%
“…The medium in the Dewar vessel could be cooled by pouring in liquid nitrogen or hydrogen. Since liquid nitrogen might absorb the neutrons appreciably, the level was kept below the bottom of the detector during measurements, a little liquid being added frequently between exposures to keep the temperature low (3). With liquid hydrogen it was found preferable to work with -D lOcro.…”
Section: Experimental Arrangementmentioning
confidence: 99%
See 1 more Smart Citation